Analisis Pemetaan Komputasi Bibliometrik Artikel Penelitian Partikel Fe2O3 Menggunakan Vosviewer - Novianti, Tria Nurwina; Nandiyanti, Asep Bayu Dani (Exact Papers in Compilation (EPiC), 2022)
This study aims to examine the development of Fe2O3 particle research with bibliometric analysis through the application of computation using VOSviewer. The article data is sourced from Google Scholar obtained with the reference manager application, publish or perish 8. The search is based on the keyword “Fe2O3, particles, paint and coating” contained in the title and abstract. The search yielded 992 articles matching keywords with a publication range from 2012 to 2022. Based on the search results, there were 240 other related items with a total link strength of 19,323 and briefly divided into 7 clusters. The results of the analysis of engineering development for the last 10 years show results that increase every year, except in 2022. This decline occurs from 2021 with 141 published articles, and in 2022, 120 articles have been published. This is based on search data as of September 2022. , so it is still possible to occur at the end of 2022. This research can be used as a prelude to research related to Fe2O3 particles.